The Influence of Communication Teamwork and Work Discipline on Employee Performance at PT. Pratomo Putra Teknik Palopo - Rika Rika; Indra Kusdarianto; Samsinar (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2023)
This study aims to determine the effect of communication teamwork and work discipline on employee performance at PT Pratomo Putra Teknik Palopo. This research method is a quantitative one, and data collection involved distributing questionnaires directly to employees of PT Pratomo Putra Teknik Palopo, with the subject of this research involving 40 respondents. In this study, using a Likert scale with a questionnaire statement, respondents answered